Humoral and cellular immune responses to CoronaVac up to one year after vaccination - Costa, Priscilla Ramos; Correia, Carolina Argondizo; Marmorato, Mariana Prado; Dias, Juliana Zanatta de Carvalho; Thomazella, Mateus Vailant; Cabral da Silva, Amanda; de Oliveira, Ana Carolina Soares; Gusmão, Arianne Fagotti; Ferrari, Lilian; Freitas, Angela Carvalho; Patiño, Elizabeth González; Grifoni, Alba; et al. (Frontiers in Immunology, 2022)
Coronavac is a widely used SARS-CoV-2 inactivated vaccine, but its long-term immune response assessment is still lacking. We evaluated SARS-CoV-2-specific immune responses, including T cell activation markers, antigen-specific cytokine production and antibody response following vaccination in 53 adult and elderly individuals participating in a phase 3 clinical trial. Activated follicular helper T (Tfh), non-Tfh and memory CD4+ T cells were detected in almost all subjects early after the first vaccine dose. Activated memory CD4+ T cells were predominantly of central and effector memory T cell phenotypes and were sustained for at least 6 months. We also detected a balanced Th1-, Th2- and Th17/Th22-type cytokine production that was associated with response over time, together with particular cytokine profile linked to poor responses in older vaccinees. SARS-CoV-2-specific IgG levels peaked 14 days after the second dose and were mostly stable over one year. CoronaVac was able to induce a potent and durable antiviral antigen-specific cellular response and the cytokine profiles related to the response over time and impacted by the senescence were defined.